The Effect of Problem-Based Learning Model of Food Cutting Competency Toward the Student Learning Outcomes of Class X at SMK YPM 2 Taman - Aprilianu, Dinia; Rijanto, Tri; Ismawati, Rita; Wiyanto, Theodorus (International Journal for Educational and Vocational Studies, 2020)
This study aims to: analyze the student learning outcomes using the problem-based learning model, compare to the student learning outcomes using the direct learning model. The type of this study is experimental research that is the factorial design. The study population is all of the students in class X. Therefore, the research sa DLMes are the students of Class X of Culinary Art 1 as the experimental class and the students of Class X of Culinary Art 2 as the control class. The researcher analyzed the data using the analysis of variance (ANOVA) two-way Anova after accoDLMishing the normality and homogeneity test requirement. Based on the result of hypothesis test using ANOVA technique, the researcher found that: (1) the student learning outcomes of cognitive aspects using problem-based learning model was significantly higher than the student learning outcomes using the direct learning model.